Administrative Courts and Clerk: a comprehensive approach to root procedural reform to implement the New Judicial Office (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this doctrinal article, I would like to analyze the operation of the Clerk of Court (Judicial Secretary) in the contentious administrative order, especially following the entry into force of Law 13/2009 of November 3. This Act amends the procedurallaw to suit the so-called “New Judicial Office,” and in particular the Law onthe Administrative Courts, Law 29/1998 of July 13. With this reform, the Clerk (Judicial Secretary), an official of a Senior Legal Corps under the Ministry of Justice, takes a definite role, responsible for all matters relating to the handling of the process that is not strictly jurisdictional. However, determining what is and what is not jurisdictional, can be complicated. These pages will attempt to shed some lighton this interesting matter.
Keywords: Administrative Courts; Clerk of Court (Judicial Secretary); Courts; Judiciary; New Judicial Office; Litigation (Procedural Law).